Isocyanates and human health: Multi-stakeholder information needs and research priorities - Lockey, JE (J Occup Environ Med, 2015)
OBJECTIVE: Outline the knowledge gaps and research priorities identified by a broad-base of stakeholders involved in the planning and participation of an international conference and research agenda workshop on isocyanates and human health held in Potomac, Maryland in April 2013. METHODS: A multi-modal iterative approach was employed for data collection including pre-conference surveys, review of a 2001 consensus conference on isocyanates, oral and poster presentations, focused break-out sessions, panel discussions and post-conference research agenda workshop. RESULTS: Participants included representatives of consumer and worker health, health professionals, regulatory agencies, academic and industry scientists, labor, and trade associations. CONCLUSIONS: Recommendations were summarized regarding knowledge gaps and research priorities in the following areas: worker and consumer exposures; toxicology, animal models, and biomarkers; human cancer risk; environmental exposure and monitoring; and respiratory epidemiology and disease, and occupational health surveillance.